New meanings in the journalistic environment: the fact-checking work of brazilian agencies amid the covid-19 pandemic : The fact-checking work of Brazilian agencies amid the covid-19 pandemic - Vieira, Marcus Vinicius de Souza (2024)
This work is focused on the specifics of the infodemic in the midst of confronting the covid-19 pandemic, in a time marked by the specifics of post-truth. The objective is to understand the extent of misinformation about the pandemic in Brazil, through the analysis of the checking work of the agencies Aos Fatos, Lupa, AFP Checamos, Projeto Comprova and G1 Fato ou Fake. In addition to the bibliographic research, a survey of checks published between August 1 and October 31, 2020 was also carried out. Based on the collection, a content analysis was carried out considering methodological categories. It is concluded that the agencies do work that is in demand, which covers different narrative formats and the classification seals consolidate the agencies as a territory of truthful information. However, the imprecision of the definitions of truth and the number of seals applied are indicative of improvements. Furthermore, the volume of misinformation circulating reinforces the need for new initiatives. Keywords:  Digital journalism; Fact-checking; Fake News; Post-truth.